A hybridization chain reaction amplification strategy for fluorescence imaging of human telomerase activity in living cells. (13th July 2018) - Zhang, Zhiqian; Zhong, Changli; Yuan, Taixian; Zhou, Xiaoyan; Zhao, Min; Qian, Husun; Cheng, Wei; Chen, Tingmei
Abstract: A hybridized chain reaction (HCR)-based biosensing method has been developed for the imaging detection of intracellular telomerase activity. The telomerase-targeting responder-transmitter DNA complex (HPT) consisting of telomerase primer sequence (HP) and a HCR initiator (trigger) is transfected into cell plasma. In the presence of telomerase, HPT can be recognized and extended, producing plenty of triggers which initiate HCR amplification reaction. Finally, a long nicked dsDNA with a lot of outstretched single chains was formed by hybridizing with Q of the reporter complex, generating an enhanced fluorescence signal. The developed biosensing approach can be used for the detection of telomerase activity in cell lysate with the detection limit of 578 cells/100 μ l. In addition, this strategy has been successfully applied not only for the sensitive and specific imaging of telomerase activity in living cells but also for comparing of telomerase activity among different cell lines. Therefore, the method might become a potential alternative tool for telomerase-related cancer diagnosis and therapy in medical research and early clinical diagnosis.